A LITERATURE REVIEW ON THE AL-HADIS AS SOURCE OF HUMAN MORAL EDUCATION - Firmansyah (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
Scope: The formation of good character that can produce an Islamic generation is not only a human being with high knowledge but also the generation of Islam includes individuals with an Islamic spirit to get happiness, progress, strength and determination. All of this is the goal of moral education. Objective: The main objective of this study is to study literature reading literature from a variety of articles, national and international journals, books and other literature and be reviewed according to the study so as to answer this Islamic research question. Method: Examining a variety of hadith literature as a source of teaching materials for the morality of the Islamic ummah in achieving life goals; prosperous and happy in the world and hereafter. The source is from a variety of reading journals and publications both at home and abroad about the virtues of al-hadith as the basic foundation of moral education so that people can answer this research problem. Finding: The findings include some of the most authentic traditions of the Prophet's companions as well as quotations of the verses of the Koran are very relevant to the citation of traditions as a guide to the moral education of humanity especially the Muslim generation. Recommendation: It is proper for moral education to be developed and developed in every community environment, both Muslims and non-Muslims, making the Prophet as the right human figure to be a role model because of the character that is reflected in each of His life.